1)y'=1 2)y'=8 3)y'=38 4)y'=-3(7x-12)+(4-3x)*7=-21x+36+28-21x=-42x+64 5)y'=9*(7-11x)+11*(9x-9)/(7-11x)^2 дальше дорешай 6)y'=54x^5-12x^3 7)y'=1/2√83+4x^2 (все под корнем)*8x=8x/√83+4x^2 8)7*(8x^3+7x^2-9)^6*24x^2+14x и там дальше дорешай 10)y'=cos(3x+2)*3=3cos(3x+2)
2)y'=8
3)y'=38
4)y'=-3(7x-12)+(4-3x)*7=-21x+36+28-21x=-42x+64
5)y'=9*(7-11x)+11*(9x-9)/(7-11x)^2 дальше дорешай
6)y'=54x^5-12x^3
7)y'=1/2√83+4x^2 (все под корнем)*8x=8x/√83+4x^2
8)7*(8x^3+7x^2-9)^6*24x^2+14x и там дальше дорешай
10)y'=cos(3x+2)*3=3cos(3x+2)